Axial compression behaviour of full-scale prefabricated wood-wool wall panel - Md Noh, Mohammad Soffi; Kamarudin, Ahmad Fahmy; Mokhatar, Shahrul Niza; Burhanudin, Mohd Khairy; Ahmad, Z.; Ibrahim, A. (Penerbit UTHM, 2020)
This study aims to investigate an axial compression behaviour of prefabricated wall constructed using wood-wool cement composite panel (WWCP). A total of three full scale wall specimens were fabricated at the laboratory with dimension of 2400 mm width, 2400 mm height and 147 mm thickness. The new fabrication technique namely as cross laminated technique was considered where the walls is fabricated using two layers of 600 mm x 2400 mm x 50 mm thickness of WWCP strips, where each layer consists of four panel strips that were arranged at cross wise panel orientation. The front and rear panel strips were bonded together using 15 mm thickness of mortar paste and as a finishing 16 mm thickness of mortar base plaster were applied on both surfaces. The prefabricated wall specimens were tested under axial compression load up to failure after 28 days of curing period. The axial load carrying capacity, vertical and lateral displacement and failure mode behaviour of walls were observed during and after test conducted. The results of experimental testing recorded that; the maximum axial compression load of prefabricated wood-wool wall specimens achieved the capacity of 1038.54 kN. This shows that the new prefabricated wall constructed using cross laminated wood-wool panel can be used as a load bearing wall system for low rise building.